Lifestyle and clinical determinants of skin autofluorescence in a population‐based cohort study. (15th April 2016) - van Waateringe, Robert P.; Slagter, Sandra N.; van der Klauw, Melanie M.; van Vliet‐Ostaptchouk, Jana V.; Graaff, Reindert; Paterson, Andrew D.; Lutgers, Helen L.; Wolffenbuttel, Bruce H. R.
Abstract: Background: Skin autofluorescence (SAF) is a noninvasive marker of advanced glycation end products (AGEs). In diabetes, higher SAF levels have been positively associated with long‐term complications, cardiovascular morbidity and mortality. Because little is known about the factors that influence SAF in nondiabetic individuals, we assessed the association of clinical and lifestyle parameters with SAF as well as their interactions in a large‐scale, nondiabetic population and performed the same analysis in a type 2 diabetic subgroup. Methods: In a cross‐sectional study in participants from the LifeLines Cohort Study, extensive clinical and biochemical phenotyping, including SAF measurement, was assessed in 9009 subjects of whom 314 (3·5%) subjects with type 2 diabetes. Results: Mean SAF was 2·04 ± 0·44 arbitrary units (AU) in nondiabetic individuals and 2·44 ± 0·55 AU in type 2 diabetic subjects ( P < 0·0001). Multivariate backward regression analysis showed that in the nondiabetic population, SAF was significantly and independently associated with age, BMI, HbA1c, creatinine clearance, genetic polymorphism in NAT2 (rs4921914), current smoking, pack‐years of smoking and coffee consumption. In the type 2 diabetic group, a similar set of factors was associated with SAF, except for coffee consumption. Conclusions: In addition to the established literature on type 2 diabetes, we have demonstrated that SAF levels are associated with several clinical and lifestyle factors in the nondiabetic population. These parameters should be taken into consideration when using SAF as a screening or prediction tool for populations at risk for cardiovascular disease and diabetes.